Projek penguatan profil pelajar pancasila (P5) dalam membentuk nasionalisme anak bangsa - Mawati, Tiarah (Maliki Interdisciplinary Journal, 2024)
This article aims to analyze the role of P5 and PPRA in fostering a sense of love for the homeland (nationalism) in the nation's children. Responding to the rapidly growing world, many children of the nation even choose foreign cultures rather than the culture of their own people. The data collection technique used is a literature review, namely by collecting various sources that are relevant and in accordance with the discussion. Then in data analysis, Miles and Huberman analysis are used which starts from data reduction, data presentation, and conclusion drawing. The result of this study is the application of P5 in forming a sense of nationalism can use one of the themes, namely engineering and technology, local wisdom, unity in diversity, or citizenship and nationality.